SOCIOLINGUISTIC PHENOMENA IN ARABIC LANGUAGE LEARNING THROUGH DIRECT METHOD - Moh. Munir (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This article was written to analyze the sociolinguistic phenomenon in the implementation of Arabic learning using the direct method at PP Al Iman Putri. This article was written using a qualitative method, with using a case study approach. The conclusion of this article shows the contribution of sociolinguistics in language learning, namely: 1) Sociolinguistics as a sub-discipline that studies language related to social factors to be the main provision for students when they continue their studies in Middle Eastern countries. 2) The Sociolinguistic Phenomenon in learning Arabic using the direct method at PP Al Iman Putri is carried out through various linguistic activities, namely: a. Morning Muhadatsah activity. b. Correction of wrong Arabic vocabulary. c. Speech activities in Arabic. d. Learning activities use Arabic (by direct method). e. The language court, which is an event deliberately held by the language department for language violators. f. Arena drama uses Arabic. g. A competition to retell an Arabic story in front of an audience, as well as a competition to deliver announcements using Arabic. h. Delivery of Arabic vocabulary. 9. Olympics of nahwu, shorof and mahfudzod.